Influence of Compression Ratio on the Combustion and Emission Behaviour of Ultrasonically Synthesised Animal-Fat Biodiesel - Javid, Abdul Hakim; Ashfaque Ahmed, S.; Nirmal Kumar, R.; Amjad Ahmed, Syed (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Animal-fat biodiesel is biodegradable, non-toxic, and offers advantages such as improved lubricity and higher cetane number when blended with diesel, while its typical drawbacks such as high viscosity and poor cold-flow behaviour can be mitigated through blending and moderate engine optimisation. In this study, a 20% animal-fat biodiesel blend (AFB20) was produced from slaughterhouse waste using base-catalysed transesterification enhanced by a 20 kHz ultrasonic-horn, which reduced reaction time from 3 hours (magnetic stirring) to 10 minutes. The ultrasonically synthesised AFB20 was tested in a single-cylinder, four-stroke, variable-compression-ratio diesel engine at compression ratios from 16.5:1 to 19.5:1. Operation at 19.5:1 was most favourable, brake specific fuel consumption improved by 6.7% relative to 16.5:1, and brake thermal efficiency increased to 35% due to enhanced atomisation. Peak cylinder pressure reached 72.76 bar and maximum heat release rate was 30.98 J/°CA, indicating shorter ignition delay. Unburnt hydrocarbons decreased by 20%, and smoke opacity reduced significantly because of better oxidation, while NOx increased moderately by about 9.5%. Overall, AFB20 operated at CR 19.5:1 demonstrated improved efficiency, lower fuel consumption, and cleaner combustion with only a moderate increase in NOx emissions, highlighting its potential as a sustainable biodiesel blend for existing stationary and agricultural diesel engines without requiring hardware modification.